2005
DOI: 10.1039/b505048k
|View full text |Cite
|
Sign up to set email alerts
|

Heck coupling of haloaromatics with octavinylsilsesquioxane: solution processable nanocomposites for application in electroluminescent devices

Abstract: A new solution processable nanocomposite material has been prepared via the Heck coupling of octavinylsilsesquioxane with a selected bromoaromatic hole transport compound. Resultant electroluminescent devices show an 18% improvement in external quantum efficiencies over their small molecule analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 19 publications
3
90
0
Order By: Relevance
“…Kleverlaan and Feilzer (2005) [14] showed that dimethacrylate composites have percentage shrinkages of 2-4% and stress values of 12-17 MPa, whereas other authors reported stress values of 6-9 MPa, and 8-12.5 MPa [26]. Thus, the material rigidity has a strong influence on the final polymerization tension [27]. As the rigidity is more associated with the crosslink density of the polymeric network than with the full conversion of the reactive species, the elastic modulus may be increased without much effect on the DC [2].…”
Section: Discussionmentioning
confidence: 81%
“…Kleverlaan and Feilzer (2005) [14] showed that dimethacrylate composites have percentage shrinkages of 2-4% and stress values of 12-17 MPa, whereas other authors reported stress values of 6-9 MPa, and 8-12.5 MPa [26]. Thus, the material rigidity has a strong influence on the final polymerization tension [27]. As the rigidity is more associated with the crosslink density of the polymeric network than with the full conversion of the reactive species, the elastic modulus may be increased without much effect on the DC [2].…”
Section: Discussionmentioning
confidence: 81%
“…Especially, performing the multiple transformations generally results in fairly low yield and remarkably difficult purification. [40,41] Constructing these complex dendritic materials conveniently with high yield and purity is thus greatly challenging.…”
Section: Star-shaped Polyfluorenesmentioning
confidence: 99%
“…21 Fourth, the functional groups are projecting in 3 dimensions thus producing a rigid spherical core from which to attach the dendrons of interest. These rigid spheres have been shown to promote amorphous properties that are known to be important for OLED devices.In continuation of our research on solution processable hybrid materials, [22][23][24] we report here the preparation of phosphorescent based CP materials for use as emissive layers in OLEDs. Our goal is to develop a platform from which many different solution processable phosphorescent materials can be prepared with optimal thermal, electronic and optical properties well suited for OLEDs.…”
mentioning
confidence: 99%